Australonema eulagiscae gen. et sp. n. (Nematoda, Marimermithida)—паразит полихеты из Антарктики - Чесунов, А.В.; Спиридонов, С.Э. (Вестник зоологии, 1985)
Australonema gen. n. is established to include A. eulagiscae sp. n.- a body cavity parasite of Eulagisca gigantea Monro. The new genus is closely related to Thalassonema, Ananus and Acronema and is characterized by the presence of mouth, channel junction of the oesophagus with intestines, normal, not trophosomized midgut, absence of the cuticular lateral pores; from Ananus it differs by head circle papillae number (10), fully developed rectum and anus, conic tail without terminal papilla.